First Use of GORE TAG Thoracic Endograft with Active Control System in Traumatic Aortic Rupture - Fotios Eforakopoulos; Ioanna Akrida; Petros Zampakis; Konstantinos Katsanos; Panagiotis Papadopoulos; Efstratios Koletsis (Case Reports in Surgery)
Patients after a high-velocity motor vehicle collision with rapid deceleration are at a significant risk of blunt aortic injury, a life-threatening condition that usually occurs in the aortic isthmus. Aortic transection is the second leading cause of death behind head injury for individuals aged 4 to 34. During the last two decades, there has been a shift from open towards the endovascular repair. Significant progress has been made recently in terms of the design of both the stent graft and the delivery system. We herein present the case of a female patient under dual antiplatelet therapy for coronary artery disease, with type IV blunt aortic injury (rupture) that was successfully repaired with Conformable Thoracic Endograft with Active Control System. This new device provides an intermediate deployment step at 50% and optional angulation control of the proximal part of the stent graft. These improvements are beneficial providing accurate device placement and maximum seal length in anatomies where the distal, as well as a proximal landing zone, is critical.